Early diagnosis of congenital methemoglobinemia type 1 in a 4-year-old child (Indian Journal of Case Reports, 2019)
Bluish discoloration of the skin and mucous membrane is known as cyanosis which is a clinical sign that occurs in many diseases. The causes of central cyanosis are cardiac shunts causing mixing of oxygenated and deoxygenated blood, lung diseases with ventilationperfusion mismatch, polycythemia, and methemoglobinemia. Methemoglobin is the oxidized form of hemoglobin, which does not bind oxygen and increases the affinity of oxygen for the partially oxidized portion of hemoglobin. Methemoglobinemia may be congenital or acquired (usually drug induced). Congenital methemoglobinemia is a very rarely reported disease that is caused by a deficiency of nicotinamide adenine dinucleotide phosphate-cytochrome b5 reductase enzyme deficiency or by an abnormal hemoglobin called hemoglobin H. Acquired methemoglobinemia is caused by drugs, namely the sulfonamide group and local anesthetics such as benzocaine and prilocaine. Here, we present the case of a 4-year-old girl who presented with complaints of bluishness of the fingers and lips without any other associated symptoms and later on diagnosed as congenital methemoglobinemia